The The Guabara Festivals (Orfeu, 2021)
This article aims to compose the narrative about the only two editions of the Festival da Guanabara, which took place in 1969 and 1970, respectively. They were events dedicated to concert music along the lines of Popular Music Festivals. Tracing this discourse was only possible by consulting the newspapers, through journalistic articles by music critics active at the time, as well as material about festivals made available by Funarte, in addition to live recordings of concerts held by the Museum of Image and Sound. Through this investigation it was possible to verify the importance of the Guanabara Festivals, not only for the history of Brazilian concert music in the second half of the XX century, as well as for the artistic-national narrative, bringing the understanding that the “Era of Festivals” also comprised two classical music events.